Analysis of the Degree of Satisfaction with Life before and during the COVID-19 Pandemic in University Teachers - Ramírez Enríquez, Silvia Isela; Barrón Luján, Juan Cristóbal; López Baca, Leopoldo Refugio; López Rodríguez, Luis Alberto; Sambrano, Gilberto Santos (European Scientific Journal, ESJ, 2022)
The objective of this work was to analyze the degree of satisfaction with the life of university teachers before and during the Covid-19 pandemic, this in the context of social isolation. The present study adopts a quantitative and cross-sectional approach, the sample is extended randomly, made up of 129 university teachers from the Faculty of Physical Culture Sciences of the Autonomous University of Chihuahua, aged between 18 and 74 years. To measure the degree of teacher satisfaction, the Satisfaction with Life Scale (SWLS) was obtained (Atienza et al., 2000; Diener et al., 1985; Pons et al., 2002). The results globally showed significant differences between life satisfaction before and during the pandemic according to the means comparison test, using the T test for related samples, with values ​​of 4.06 before and 3.6 during the pandemic. When carrying out the categorization of the results according to the escalation, it was shown that 55.7% of the teachers perceived themselves satisfied before the pandemic, the opposite happening during the isolation, decreasing, only 45.5% feeling satisfied. Only 27% felt very satisfied before and this percentage decreased to only 14.5% during isolation. The Covid-19 not only wreaked havoc on health, but also negative effects on people’s psychological, emotional and social spheres, thus modifying healthy lifestyles and leaving possible effects on physical and mental health as a consequence.